2023
DOI: 10.1097/corr.0000000000002598
|View full text |Cite
|
Sign up to set email alerts
|

What is the Safe Distance Between Hip and Knee Implants to Reduce the Risk of Ipsilateral Metachronous Periprosthetic Joint Infection?

Abstract: Background Periprosthetic joint infection (PJI), the most common cause of revision after TKA and THA, is a devastating complication for patients that is difficult to diagnose and treat. An increase in the number of patients with multiple joint arthroplasties in the same extremity will result in an increased risk of ipsilateral PJI. However, there is no definition of risk factors, micro-organism patterns, and safe distance between knee and hip implants for this patient group. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…In their current work in Clinical Orthopaedics and Related Research ® , Akkaya et al [1] present an interesting and very relevant perspective about periprosthetic joint infection (PJI) by looking at the unusual (but not rare) setting of ipsiplateral THA and TKA. The paper, from the laboratory of Professor Mustafa Citak, arises from an analysis of insitutional data collected at the world-renowned ENDO-Klinik in Germany.…”
Section: Where Are We Now?mentioning
confidence: 99%
See 3 more Smart Citations
“…In their current work in Clinical Orthopaedics and Related Research ® , Akkaya et al [1] present an interesting and very relevant perspective about periprosthetic joint infection (PJI) by looking at the unusual (but not rare) setting of ipsiplateral THA and TKA. The paper, from the laboratory of Professor Mustafa Citak, arises from an analysis of insitutional data collected at the world-renowned ENDO-Klinik in Germany.…”
Section: Where Are We Now?mentioning
confidence: 99%
“…Equally, how does the central European experience translate to the North American, Oceania, and Asian settings (acknowledging differences in populations, resource availability, healthcare system structures and clinical care paradigms)? Of equal importance, approaches to the diagnosis of PJI have evolved since 2010 (which is when retrospective patient inclusion began in this study [1]) —in particular, the trend toward adoption of standardized diagostic methods such as the updated Musculoskeletal Infection Society criteria (2018) [8]. This raises fair questions as to whether concurrent infections may have been missed in this report; future studies should therefore seek to replicate or refute these findings.…”
Section: Where Do We Need To Go?mentioning
confidence: 99%
See 2 more Smart Citations
“…Unexpectedly, the investigators found that the associations (regressions) between the coefficient-of-variation tertiles and complication, PJI, mortality, and non-home discharge variables were not significant in revision TKA, although they argued that the relatively small sample size (n = 636) was responsible for these findings. Factors associated with the development of subsequent PJI among patients with ipsilateral hip and knee arthroplasties who initially experienced infection of 1 of the implants were addressed by Akkaya et al 58 . Patients who developed ipsilateral metachronous PJI had significantly shorter stem-to-stem (tip-to-tip) distances (8 compared with 14 cm; p < 0.01) and empty (no foreign body such as cement) native bone distances (5 compared with 11 cm; p < 0.01), as well as an elevated risk of cement extrusion beyond its restrictor (70% compared with 5%; p < 0.01) compared with patients who did not develop infection.…”
Section: Revision Tkamentioning
confidence: 99%